2018
DOI: 10.1186/s13756-018-0345-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, identification of virulence factors, O-serogroups and antibiotic resistance properties of Shiga-toxin producing Escherichia coli strains isolated from raw milk and traditional dairy products

Abstract: BackgroundShiga-toxigenic Escherichia coli strains are one of the most important foodborne bacteria with an emergence of antibiotic resistance. Foodborne STEC strains are mainly associated with presence of certain virulence factors and O-seogroups. The present investigation was done to study the distribution of virulence factors, O-serogroups and antibiotic resistance properties of Shiga-toxigenic Escherichia coli isolated from milk and dairy products.MethodsSix-hundred samples were randomly collected and imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
75
6
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 54 publications
14
75
6
2
Order By: Relevance
“…In despite of the high importance of H. pylori , occurrence and antibiotic resistance of other foodborne pathogens have been reported previously from Iran (Madahi, Rostami, Rahimi, & Dehkordi, ; Momtaz, Davood Rahimian & Safarpoor Dehkordi, 2013; Momtaz, Dehkordi, Rahimi, Asgarifar, & Momeni, ; Momtaz, Safarpoor Dehkordi, Taktaz, Rezvani, & Yarali, ; Rahimi, Yazdanpour, & Dehkordi, ; Ranjbar, Masoudimanesh, Dehkordi, Jonaidi‐Jafari, & Rahimi, ; Ranjbar, Safarpoor Dehkordi, Sakhaei Shahreza, & Rahimi, , Ranjbar, Yadollahi Farsani, et al, ; Safarpoor Dehkordi, Barati, et al, ; Safarpoor Dehkordi, Gandomi, Akhondzadeh Basti, Misaghi, & Rahimi, ; Safarpoor Dehkordi, Haghighi, Momtaz, Rafsanjani, & Momeni, ; Safarpoor Dehkordi, Khamesipour, & Momeni, ; Safarpoor Dehkordi et al, ; Safarpoor Dehkordi, Valizadeh, Birgani, & Dehkordi, ).…”
Section: Resultsmentioning
confidence: 98%
“…In despite of the high importance of H. pylori , occurrence and antibiotic resistance of other foodborne pathogens have been reported previously from Iran (Madahi, Rostami, Rahimi, & Dehkordi, ; Momtaz, Davood Rahimian & Safarpoor Dehkordi, 2013; Momtaz, Dehkordi, Rahimi, Asgarifar, & Momeni, ; Momtaz, Safarpoor Dehkordi, Taktaz, Rezvani, & Yarali, ; Rahimi, Yazdanpour, & Dehkordi, ; Ranjbar, Masoudimanesh, Dehkordi, Jonaidi‐Jafari, & Rahimi, ; Ranjbar, Safarpoor Dehkordi, Sakhaei Shahreza, & Rahimi, , Ranjbar, Yadollahi Farsani, et al, ; Safarpoor Dehkordi, Barati, et al, ; Safarpoor Dehkordi, Gandomi, Akhondzadeh Basti, Misaghi, & Rahimi, ; Safarpoor Dehkordi, Haghighi, Momtaz, Rafsanjani, & Momeni, ; Safarpoor Dehkordi, Khamesipour, & Momeni, ; Safarpoor Dehkordi et al, ; Safarpoor Dehkordi, Valizadeh, Birgani, & Dehkordi, ).…”
Section: Resultsmentioning
confidence: 98%
“…Enterohemorrhagic E. coli (EHEC) bacteria are a dangerous phenomenon originated from Shiga toxin-producing E. coli (STEC) [3][4][5]. They are accountable for hemolytic uremic syndrome (HUS), thrombotic thrombocytopenic purpura (TTP), hemorrhagic colitis (HC) and diarrhea [6,7]. O157 is a chief serogroup of the above mentioned phenomena with boost clinical standing [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…They are accountable for hemolytic uremic syndrome (HUS), thrombotic thrombocytopenic purpura (TTP), hemorrhagic colitis (HC) and diarrhea [6,7]. O157 is a chief serogroup of the above mentioned phenomena with boost clinical standing [3][4][5][6][7]. Poultry is one of the most significant sources of human infection [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with the high nutritional importance of dairy products (Thorning et al, 2016), dairy products are not essentially safe, as demonstrated by higher rates of foodborne illnesses associated with their consumption (Momtaz, Safarpoor Dehkordi, Taktaz, Rezvani, & Yarali, 2012;Rahimi, Sepehri, Dehkordi, Shaygan, & Momtaz, 2014;Ranjbar, Dehkordi, Shahreza, & Rahimi, 2018;Safarpoor Dehkordi, Barati, Momtaz, Hosseini Ahari, & Nejat Dehkordi, 2013;Safarpoor Dehkordi, Valizadeh, Birgani, & Dehkordi, 2014). As well, there were so many investigations about the considerable incidence of some specific foodborne pathogens in dairies (Momtaz et al, 2012;Ranjbar, Yadollahi Farsani, & Safarpoor Dehkordi, 2018;Safarpoor Dehkordi et al, 2013;Safarpoor Dehkordi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%